PENERAPAN MODEL PEMBEAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 013 BAGAN HULU - Monaliza '; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Learning science class III SDN 013 Bagan Hulu is low, this is caused by the learning is done by texs oriented book, using the lecture method (conventional) and exercises with student involvement was minimal and many current students passive learning. This study aims to improve student learning outcomes SDN 013 Class III Bagan Hulu through the School Year 2015/2016